TRUST MEMEDIASI HUBUNGAN PERSEPSI USER DAN KOMITMEN KARYAWAN TERHADAP LOYALITAS PENGGUNA TENAGA KERJA OUTSOURCING - Martini, Ida Ayu Oka (Universitas Pendidikan Nasional, 2018)
Trust Memediasi Hubungan Persepsi User dan Komitmen Karyawan Terhadap LoyalitasPengguna Tenaga Kerja Outsourcing.This research was conducted to find out whether there was effect of user perception and commitment to user loyalty with trust as variable intervening at PT.Bali Dana Sejahtera. Bali Dana Sejahtera is one of outsourcing company with almost 300 outsourcing employees. Samples were obtained by 50 samples from 200 employees of outsourcing user at PT. Bank BPD Bali Head office, Renon dan Denpasar. The data analysis technique uses the SPSS. Analysis of the data used in this study includes instrument testing,Path Analysis. The results of this study found that user perception and commitment was affected on trust .The second result is user perception, commitment and trust was affected on user loyalty. This can be seen from the results of path analysis that has been processed using SPSS. Validation test on each path for direct influence is the same as regression, using p value from t test which is testing the variable regression coefficient partially proven from user's perception (X1) of trust (Y1) is 0.294 sig 0.007, commitment (X2) to trust (Y1) is 0.649 with sig 0,000, user perception variable (X1) to user loyalty (Y2) is 0.404 with sig 0,000. Commitment variable (X2) to user loyalty (Y2) is 0.620 with sig 0,000, trust variable (Y1) to user loyalty (Y2) is 0.268 with sig 0.001.Keywords: User perception, commitment, trust, user loyalty, outsourcing